2018
DOI: 10.11622/smedj.2017046
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography of the head for adult patients with minor head injury: are clinical decision rules a necessary evil?

Abstract: Compliance with the CCHR for adult patients with minor head injury remains low in the ED. A qualitative review of physicians' practices and patients' preferences may be carried out to evaluate reasons for noncompliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 21 publications
6
20
0
Order By: Relevance
“…(4) Tan et al conducted a retrospective analysis of 349 patients on the compliance and performance of the CCHR. (5) Compliance to the rule was at 71.3%, which was comparable to the rate reported in Canada. Among the 8.6% of patients for whom CT was recommended but not performed, none had clinically significant head injury.…”
supporting
confidence: 70%
“…(4) Tan et al conducted a retrospective analysis of 349 patients on the compliance and performance of the CCHR. (5) Compliance to the rule was at 71.3%, which was comparable to the rate reported in Canada. Among the 8.6% of patients for whom CT was recommended but not performed, none had clinically significant head injury.…”
supporting
confidence: 70%
“…Previous research has shown a low compliance with the clinical rules to select TBI patients for head CT, ranging around 15-60%. [33][34][35][36] Physicians are often either unaware of the clinical decision rules or ignore them in clinical practice due to their complexity. 34,36,37 In agreement with past literature, 6,9,38,39 our study found all four clinical decision rules to have excellent NPV but low PPV.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Although the Canadian head CT rule and the New Orleans Criteria offer some guidelines, they primarily rely on additional methods to support the evaluation of TBIs. [29][30][31] Hence, when a patient presents with facial trauma, which is common among TBI patients, measuring both ONSD and ONST may prove necessary to help clinicians decide whether to request additional brain CTs. Based on the results of the present study, we recommend that ONST on sagittal facial CT images be assessed prior to prescribing any additional brain CT, especially when novice EPs are involved in the patient's care.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients without suspected TBI, additional radiologic evaluation may not be required, because of the risk of increased radiation exposure, especially among vulnerable patients such as children and pregnant women, followed by an increase in medical costs [ 27 , 28 ]. Although the Canadian head CT rule and the New Orleans Criteria offer some guidelines, they primarily rely on additional methods to support the evaluation of TBIs [ 29 - 31 ]. Hence, when a patient presents with facial trauma, which is common among TBI patients, measuring both ONSD and ONST may prove necessary to help clinicians decide whether to request additional brain CTs.…”
Section: Discussionmentioning
confidence: 99%